Proximate Composition of Shell (Bivalves) in North Aceh District, Aceh Province Based on Differences in Species and Environmental Characteristics - Erniati Erniati; Yudho Andika; Imanullah Imanullah; Imamshadiqin Imamshadiqin; Salmarika Salmarika; Cut Meurah Nurul ‘Akla; Elva Dwi Yulistia; Sanja Maulana; Rafly Lazuardy (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
Shellfish (bivalves) are potential biodiversity of waters with an important significant value used by the community as a food source of highly nutritious animal protein. Based on survey results, several coastal areas in North Aceh District have the potential for shellfish. Still, there have not been any scientific reports on this region's proximate composition of bivalves. This study aims to determine the relative arrangement of the dominant bivalves in the North Aceh District based on species differences and environmental characteristics. The results showed varying proximate bivalve proximate compositions of 4 chief types of shellfish in North Aceh waters. Bivalvia water ranged from 6.9-14.2%, ash ranged from 5.87-8.29%, protein ranged from 32.84-35.87%, fat ranged from 3.04-10.83%, and carbohydrate ranged from 38.11-42.71%. The highest protein and fat content were found in the Crassostrea sp1 type clams. In addition, the differences in the environmental characteristics of the shell sampling locations also resulted in different proximate compositions. The PCA test results showed that the critical variablarrangemente composition was ash and fat content. The environmental parameters, which were the key parameters of the relative arrangement of the shells were the substrate and pH.